Design a Optimum MPPT Controller for Solar Energy System - F. R. Islam; K. Prakash; K. A. Mamun; A. Lallu; R. Mudliar (Institute of Advanced Engineering and Science, 2016)
Solar energy is compared to be the best potential source of renewable energy in Pacific region. For this reason a photovoltaic cell is needed to harvest this kind of energy, gathering the most of it and the PV having a good efficiency. The maximum efficiency is achieved when the PV works at its Maximum Power Point which entirely depends on the irradiation and temperature. This paper proposes a new design of hybrid Maximum Power Point Tracking and a comparative study is made with various existing MPPT techniques which include Perturb and Observe method, Incremental Conductance and Fuzzy Logic. From the comprehensive comparison study between existing MPPT technique and the proposed MPPT technique/theory, a hardware setup was demonstrated to verify the proposed design by charge controller in photovoltaic systems to which maximize the output power under various lighting conditions. The design is based on the computed results using the buck-boost DC-DC conveter. From the simulation, the proposed method tends to show better performance with almost no oscillations around the MPP.